Use of mineral oil as skin moisturizer and evaluated by using Dermalab® Combo - A. K., Azad; Wan Sulaiman, Wan Mohd Azizi; N. Z, Ismail; Shaha, Shyam Sundor; Sunzida, Nushrat Khan (Pharmaceutical Research Information Group, 2016)
Objective: This particular study aims to investigate the effect of mineral oil in different products on the barrier function of normal skin, as measured by transepidermal water loss (TEWL) and hydration. In this study, 15 female Methods: volunteers were divided into three groups, which corresponded with three different brands of moisturizers. The volunteers were treated with one test preparation on one volar forearm twice daily for 3 weeks, while leaving the other forearm untreated to serve as the control. After 3 weeks, both volar forearms, treated and control, were assessed for the measurement of TEWL and hydration by using DermaLab® Combo, and the readings were compared to the baseline. Results: Changes were observed after 3 weeks treatment of mineral oil-based moisturizers, in which both TEWL and hydration increased for both control and test sides, but the percentage of increment was lower than that observed with test side. TEWL Moisturizers influence the skin barrier function of normal skin, as measured by TEWL and hydration. readings of all subjects for all the three types of products increased significantly from the baseline This . Conclusions: results shows that the side treated with mineral-oil based moisturizers were able to promote greater degree of skin hydration compared to the untreated side